Intimate Relations: Psychoanalysis Deconstruction / La psychanalyse la déconstruction - Rottenberg, Elizabeth (Bollettino Filosofico, 2021)
This essay will concentrate, somewhat voyeuristically, on a particular and very special textual encounter. For if there is one text in the psychoanalytic tradition that will have caused Derrida to spill more ink than any other. It’s Freud’s Beyond the Pleasure Principle (1920). For ten years, from 1970-1980, Derrida returns not once but three times, on three separate occasions, in three different contexts, to Freud’s text on repetition compulsion and the death drive, each time devoting more time and energy, that is to say, more pages to it. As we will see in this essay, what emerges from this textual encounter is not only a new kind of pleasure; it is also a chance event of repetition that brings with it something strikingly new. Keywords: Fort/Da, Freuderrida, Play, Pleasure, Speculation